A life-long neurology - P. N. Vlasov (Эпилепсия и пароксизмальные состояния, 2021)
A multi-year career path and overwhelmingly rich legacy of Professor V.A. Karlov are presented in the report. Prominent publications related to the main research directions of his work as an outstanding scientist and clinician are outlined.